ANALISIS PESAN MOTIVASI DALAM FILM “RENTANG KISAH” (PENDEKATAN TEORI ABRAHAM MASLOW) - Suci Ramadhani, Dela; Yoserizal Saragih, M; Fatra Deni, Indira (Lafadz Jaya Publisher, 2023)
The purpose of this study is to find out how the motivational messages in the film